2020
DOI: 10.1021/acsabm.0c00578
|View full text |Cite
|
Sign up to set email alerts
|

Polynorepinephrine as an Efficient Antifouling-Coating Material and Its Application as a Bacterial Killing Photothermal Agent

Abstract: Biomedical device-related infection (BDI) is of great concern in modern clinical and medical applications. Various approaches to combat BDI are based on two major principles: the prevention of biofoulants adhering on medical devices and the ability to eradicate biofouling once formed. To minimize the risk of BDI, an antifouling coating with bactericidal ability is highly desirable. In this work, we report on the use of polynorepinephrine (PNE) as a promising strategy to prevent BDI due to its excellent antifou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We used a fluorescein-conjugated bovine serum albumin (FITC-BSA) and GFP to simulate the fouling process as these proteins are generally used to evaluate the protein fouling capability of biomaterials. , Upon soaking the coated substrate and control material (1 × 1 cm 2 ) in protein solution (0.2 mg/mL) for 3 h at 37 °C, the surface was imaged by confocal laser scanning microscopy (CLSM), and the corresponding fluorescence intensity was quantified by ImageJ software. In the case of FITC-BSA, we observed a bright green color in the control sample, which confirms the occurrence of protein adsorption on the PSt surface.…”
Section: Resultsmentioning
confidence: 99%
“…We used a fluorescein-conjugated bovine serum albumin (FITC-BSA) and GFP to simulate the fouling process as these proteins are generally used to evaluate the protein fouling capability of biomaterials. , Upon soaking the coated substrate and control material (1 × 1 cm 2 ) in protein solution (0.2 mg/mL) for 3 h at 37 °C, the surface was imaged by confocal laser scanning microscopy (CLSM), and the corresponding fluorescence intensity was quantified by ImageJ software. In the case of FITC-BSA, we observed a bright green color in the control sample, which confirms the occurrence of protein adsorption on the PSt surface.…”
Section: Resultsmentioning
confidence: 99%
“…While the search and syntheses of elusive ''all-in-one'' antimicrobial agents or antimicrobial delivery systems appears to be a long and difficult path, designing delivery systems for particular applications and treatments by changing the biopolymer or biomolecule compositions of the encapsulants seem to be a more practical option, particularly in this race against antimicrobial resistance. Tuning the drug delivery system components also seems to be a very attractive approach to create opportunities for on-demand localisation and/or release via external triggers or stimuli (heat, [91][92][93] light, [94][95][96] magnetic field, [97][98][99] ultrasound, 100-103 etc.). The growing knowledge on these biomacromolecules and other nanomaterials is an opportunity that can be extended to other types of colloidal delivery systems, such as emulsion droplets, micro-and nanobubbles, and composite materials that can be fabricated with these colloids, including antimicrobial surfaces and coatings, fibres, gels, and implant-type biomedical devices.…”
Section: Discussionmentioning
confidence: 99%
“…32 Besides this, our group also demonstrated that PNE coated coverslips show great protein resistance capability and remarkable bacterial elimination ability after being irradiated with NIR, further indicated PNE's potential at combating biomedical device related infections. 50…”
Section: Pne Antifouling Coatingsmentioning
confidence: 99%